Mythologies, Identities and Territories of Photography : Forever//Now (Cambridge Scholars Publishing, 2020)
This book brings together essays by both experienced and emerging researchers, photographic artists, and curators exploring themes such as ethnicity, gender, materiality, the archive, memory, age, national identity, and technologies, with several papers discussing creative responses to the UK's departure from the European Union. In addition, it includes a paper by Martin Barnes, Senior Curator of Photography at the Victoria and Albert Museum, on the work of industrial photographer, Maurice Broomfield. The book will appeal to students, academics, photographic artists, curators, and those with an.